Mainstreaming Justice in the Establishment of Laws and Regulations Process: Comparing Case in Indonesia, Malaysia, and Australia - Rodiyah Rodiyah; Siti Hafsyah Idris; Robert Brian Smith (Universitas Negeri Semarang, 2023)
This paper compares the cases of Indonesia, Malaysia, and Australia to examine how these countries incorporate principles of justice in the establishment of laws and regulations. It explores the significance of mainstreaming justice in lawmaking, emphasizing equitable representation, fair access to justice, and human rights considerations. The analysis highlights the legal frameworks and institutional structures in each country. In Indonesia, the role of the Constitutional Court and stakeholder involvement in the legislative process are examined. Malaysia's constitutional framework and efforts to address ethnic and religious diversity, as well as the role of judicial review, are discussed. Australia's common law system emphasizes parliamentary scrutiny, public consultations, and protection of individual rights through the High Court and parliamentary committees. This study provides insights into the diverse approaches and challenges faced by these countries in mainstreaming justice in their lawmaking processes. It contributes to understanding how justice can be effectively integrated into laws and regulations, offering valuable insights for policymakers and legal practitioners seeking to promote justice in legislative contexts.